2015
DOI: 10.1017/s0007114514003663
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between socio-economic status and dietary patterns in European children: the Identification and Prevention of Dietary- and Lifestyle-induced Health Effects in Children and Infants (IDEFICS) Study

Abstract: Exploring changes in children's diet over time and the relationship between these changes and socio-economic status (SES) may help to understand the impact of social inequalities on dietary patterns. The aim of the present study was to describe dietary patterns by applying a cluster analysis to 9301 children participating in the baseline (2 -9 years old) and follow-up (4-11 years old) surveys of the Identification and Prevention of Dietary-and Lifestyle-induced Health Effects in Children and Infants Study, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 38 publications
7
72
0
2
Order By: Relevance
“…We found that daily food and drink intake is relatively stable across the ages of 2 to 4.5 years, in general agreement with data from longitudinal studies conducted in Europe [10, 14]. However, it was concerning that the young children mostly added energy-dense foods of low nutritional value (refined grains, discretionary fat and condiments, and desserts and sweets) as they grew older.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that daily food and drink intake is relatively stable across the ages of 2 to 4.5 years, in general agreement with data from longitudinal studies conducted in Europe [10, 14]. However, it was concerning that the young children mostly added energy-dense foods of low nutritional value (refined grains, discretionary fat and condiments, and desserts and sweets) as they grew older.…”
Section: Discussionsupporting
confidence: 87%
“…SES is a multidimensional construct that conveys relative wealth, power, and prestige, and it is influenced by race, ethnicity, parental education, occupation, and income. It is also a strong determinant of health [7] and has been repeatedly linked to diet quality [814]. Importantly, the association between SES and a health outcome can differ depending on how SES is measured [15].…”
Section: Introductionmentioning
confidence: 99%
“…Sobre las alteraciones nutricionales que pudieran presentarse en menores de 5 años, influyen varios factores, entre ellos, el nivel de educación de los progenitores especialmente de la madre, y el estrato (5,9) socioeconómico . Al comparar los promedios de los años de estudios de la madre según el estado nutricional de sus hijos/as, no se encontraron diferencias significativas entre los grupos de madres con mayor o menor tiempo de asistencia a alguna institución de enseñanza.…”
Section: Discussionunclassified
“…In turn, decreased pulmonary reserve capacity might then predispose an individual to COPD later in life [19]. Sociological mechanisms in adulthood may promote smoking habits [20], low physical activity, and inappropriate nutrition [21] in people with low SEP. These factors alone or in combination with harmful occupational exposures [22], air pollution [23, 24], and reduced access to appropriate health care and medication may also increase risk of developing COPD in people with low SEP [2].…”
Section: Introductionmentioning
confidence: 99%